Global autism prevalence, and exploring Montessori as a practical educational solution: a systematic review - Ying Li (Frontiers in Psychiatry)
IntroductionAutism spectrum disorder (ASD) is a neurodevelopmental condition that impairs social interaction, communication, and appropriate behavior.MethodsOut of 1,740 articles initially identified through electronic databases using PRISMA guidelines and the PICOS framework, only 15 met the inclusion criteria for this review.ResultsAlthough the precise etiology of autism remains unclear in most cases, from cohort studies, the heritability as a potential cause is estimated to range between 50% and 80%, taking into account consistent environmental risk factors such as parental age, pollution, and maternal infections during pregnancy. Several autism-related gene mutations have also been identified. Recommended interventions include applied behavior analysis, speech therapy, pharmacological treatment, and emerging techniques such as artificial intelligence, virtual reality, and microbiome-based approaches. Pharmacological agents like Risperidone and Aripiprazole can alleviate specific symptoms but do not target the core features of ASD. Additional evidence-based therapies, including occupational therapy and sensory integration, have demonstrated benefits in enhancing functional outcomes.DiscussionMontessori education, a sensory-focused, individualized, and play-based learning approach, aligns well with the individual learning needs of ASD and shows considerable potential in improving communication and social skills in children with ASD. This systematic review underscores geographic disparities and risk factors associated with autism while uniquely assessing Montessori education as a promising intervention, paving the way for further research in low-resource settings.